The Use of Exosomes in Clinical Applications, With an In-Depth Look at Those Derived From Mesenchymal Stem Cells and Their Use in Myocardial Regeneration - Al-Sowayan, Batla (International Journal of Innovative Research in Medical Science, 2017)
Many mesenchymal stem cell (MSC)-based clinical trials are targeted toward cardiovascular diseases, specifically cardiac ischemia. Investigatory work has revealed that MSC-produced “exosomes” are in fact the element that initiates tissue restoration. This, in addition to the advantages of using exosomes over transplanting whole cells, makes “MSC-exosome-based therapy” a very appealing concept. This review will discuss exosomes and their possible clinical applications, with particular emphasis on MSC-derived exosomes and their use in managing ischemic myocardial damage.